Perilaku Politik Masyarakat Pulau Rajuni Kecamatan Takabonerate pada Pemilukada Selayar 2020 - Maulani, Madpirah; Yunus, Ariana; Nadir, Sakinah (Universitas Musamus, Merauke, Papua, 2024)
This research explores the political behavior and political participation of the Rajuni Village community in Takabonerate Sub-district, Selayar Islands Regency, South Sulawesi, in the context of the 2020 Regional Head Election. Using a qualitative approach and a case study design, this research explores the factors that influence political choices and the level of community participation in 3T (Disadvantaged, Frontier and Outermost) areas. Data were collected through in-depth interviews with Rajuni villagers, community leaders, village officials, and representatives of non-governmental organizations. Data analysis included three stages: data reduction, data presentation, and conclusion drawing. The results showed that the political choices of the Rajuni Island community were influenced by money politics, political awareness, and mobilization by local figures. The Bugis tribe is more likely to be influenced by money politics with a Rational Choice approach. Political awareness is also important, where voters consider the vision, mission and programs of candidates that are relevant to their needs. Mobilization by economically influential local figures also influences political choices. The level of political participation of the Rajuni Island community is quite high, reaching 70% in the 2018 Governor Election and the 2020 Selayar Islands Regency Regent Election. This research provides insights into political behavior and community participation in an archipelago with significant geographic and social challenges.